Rancang Bangun Alat Pencahayaan Terkontrol Berbasis Motor Stepper Dan Railing untuk Studio Fotografi - Christiand; Djoko Setyanto; Anthon De Fretes; Joseph Prabaswara Astadiningrat; Feryandinata Indrajaya; Rangga Dewata Putra (Program Studi Teknik Industri, Fakultas Teknik, Universitas Katolik Indonesia Atma Jaya Jakarta, 2025)
Photography studios often require various lighting arrangements for different photo and video shooting themes. Lighting in a studio environment is critical to producing high-quality images and videos. However, conventional lighting sources, such as lamps or other lighting equipment, are often inflexible to reposition according to the photographer’s desired thematic setup. Manual lighting adjustments can be time-consuming, mainly when automated positioning features are unavailable. This inefficiency hampers the photo and video shooting process. In the community service program discussed in this article, the team from the Mechanical Engineering Department at Atma Jaya Catholic University of Indonesia developed a motorized stepper-based lighting system with railing to address the inefficiencies in studio lighting adjustments. The team partnered with Kolaborasi Berkat Kreasindo (KBK) studio. The developed lighting system can be controlled remotely, eliminating the need for direct manual adjustments. This solution has assisted the partner studio in enhancing the lighting setups for photography sessions.